An Overview of Inborn Errors of Metabolism manifesting with Primary Adrenal Insufficiency - Hannah-Shmouni, Fady (Rev Endocr Metab Disord, 2018)
Primary adrenal insufficiency (PAI) results from an inability to produce adequate amounts of steroid hormones from the adrenal cortex. The most common causes of PAI are autoimmune adrenalitis (Addison disease), infectious diseases, adrenalectomy, neoplasia, medications, and various rare genetic syndromes and inborn errors of metabolism that typically present in childhood although late-onset presentations are becoming increasingly recognized. The prevalence of PAI in Western countries is approximately 140 cases per million, with an incidence of 4 per 1,000,000 per year. Several pitfalls in the genetic diagnosis of patients with PAI exist. In this review, we provide an in-depth discussion and overview on the inborn errors of metabolism manifesting with PAI, including genetic diagnosis, genotype-phenotype relationships and counseling of patients and their families with a focus on various enzymatic deficiencies of steroidogenesis.